Genetic variation within the genus Macropostrongyloides (Nematoda: Strongyloidea) from Australian macropodid and vombatid marsupials. Issue 13 (28th August 2019) - Sukee, Tanapan; Beveridge, Ian; Chilton, Neil B.; Jabbar, Abdul
Abstract: The genetic variation and taxonomic status of the four morphologically-defined species of Macropostrongyloides in Australian macropodid and vombatid marsupials were examined using sequence data of the ITS+ region (=first and second internal transcribed spacers, and the 5.8S rRNA gene) of the nuclear ribosomal DNA. The results of the phylogenetic analyses revealed that Ma. baylisi was a species complex consisting of four genetically distinct groups, some of which are host-specific. In addition, Ma. lasiorhini in the common wombat ( Vombatus ursinus ) did not form a monophyletic clade with Ma. lasiorhini from the southern hairy-nosed wombat ( Lasiorhinus latifrons ), suggesting the possibility of cryptic (genetically distinct but morphologically similar) species. There was also some genetic divergence between Ma. dissimilis in swamp wallabies ( Wallabia bicolor ) from different geographical regions. In contrast, there was no genetic divergence among specimens of Ma. yamagutii across its broad geographical range or between host species (i.e. Macropus fuliginosus and M. giganteus ). Macropostrongyloides dissimilis represented the sister taxon to Ma. baylisi, Ma. yamagutii and Ma. lasiorhini . Further morphological and molecular studies are required to assess the species complex of Ma. baylisi .